2007
DOI: 10.1080/13573320701464275
|View full text |Cite
|
Sign up to set email alerts
|

Friendship, physicality, and physical education: an exploration of the social and embodied dynamics of girls’ physical education experiences

Abstract: Physical education represents a dynamic social space where students experience and interpret physicality in a context that accentuates peer relationships and privileges particular forms of embodiment. This article focuses on girls' understandings of physicality with respect to the organisation of physical education and more informal social networks. Research exploring the connections between the body, capital, physical activity, and femininity and work on friendship and other social relationships underpin the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 36 publications
10
74
0
21
Order By: Relevance
“…The significance of physical skills for the recognition and participation of students in PE have also been described by others (Carlson, 1995;Griffin, 1984Griffin, , 1985Grimminger, 2013;Grimminger 2014b, Hills, 2007Portman, 1995aPortman, , 1995b. Even if physical skills are undoubtedly important for the legitimacy ascribed to students, in our observations and interviews with students it also became clear that students' physical skills were neither a guarantee nor a prerequisite for the legitimacy ascribed.…”
Section: We Give Them the Ball But They Give It Back To Us Straight mentioning
confidence: 65%
See 3 more Smart Citations
“…The significance of physical skills for the recognition and participation of students in PE have also been described by others (Carlson, 1995;Griffin, 1984Griffin, , 1985Grimminger, 2013;Grimminger 2014b, Hills, 2007Portman, 1995aPortman, , 1995b. Even if physical skills are undoubtedly important for the legitimacy ascribed to students, in our observations and interviews with students it also became clear that students' physical skills were neither a guarantee nor a prerequisite for the legitimacy ascribed.…”
Section: We Give Them the Ball But They Give It Back To Us Straight mentioning
confidence: 65%
“…So the relations between the girls and between Michael and the girls hamper Michael's participation, placing him in a peripheral position (upper corner field 2, Figure 2) and at risk of being marginalised (lower corner field 2, Figure 2) in this specific case. The significance of social relations or popularity among peers has also been reported in studies by Hills (2007), Grimminger (2013) and O'Donovan (2003). Hills (2007) found that girls' physical skills, as well as girls' social relationships, were important in shaping their involvement in PE and for the power relations between the included and the excluded students.…”
Section: We Give Them the Ball But They Give It Back To Us Straight mentioning
confidence: 89%
See 2 more Smart Citations
“…Ideally, physical education was used as a platform to provide students with the chance to acquire and develop motor skills, build selfesteem, gain knowledge through physical activity, collaborate with peers as well as to participate in an enjoyable learning environment [10].…”
Section: Introductionmentioning
confidence: 99%